Numerical simulation and experimental comparison of flaw evolution on a bearing raceway: Case of thrust ball bearing. Issue 4 (31st January 2018) - Toumi, M.Y.; Murer, S.; Bogard, F.; Bolaers, F.
Graphical Abstract: Abstract: Bearings are essential elements in the design of rotating machines. In an industrial context, bearing failure can have costly consequences. This paper presents a study of the rolling contact fatigue damage applied to thrust ball bearings. It consists in building a dynamic three-dimensional numerical model of the cyclic shift of a ball on an indented rolling surface, using finite element analysis (FEA). Assessment of the evolution in size of a surface spall as a function of loading cycles is also performed using FEM coupled with fatigue laws. Results are in good agreement with laboratory tests carried out under the same conditions using a fatigue test cell dedicated to ball bearings. This study may improve knowledge about estimating the lifetime of rolling components after onset of a spall using FEA and accounting for structural damage state.